The use of maker culture in a socio-educational environment (Research, Society and Development, 2024)
The objective of this article is to present an action research study of the project that aimed to use, within the maker culture, playful materials adapted in the educational context. In this case, it stands out in basic education in its entirety, with the intention of expanding and improve the teaching-learning process, as well as putting into practice teaching methodologies and/or active methodologies that they can use during the academic year and included in interdisciplinary activities, as a way of assisting teachers in their teaching methodology, and consequently, expanding the student's potential and skills. From this perspective, the maker culture, within its possibilities and experimentation, can create original means so that the student can create, recreate and develop projects using everyday materials including laser printing machines. The maker culture highlights the breadth of information and human knowledge, capable of creating, copying and recreating, providing students with the knowledge and practice necessary to begin their inclusion in the job market, and in the case of the participants in this project, the their resocialization.